Gendered Language Use In Academic And Professional Settings - Karimova, Ozodaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Gendered language use has become a significant focus in applied linguistics, reflecting how linguistic choices construct, reproduce, or challenge social identities in academic and professional contexts. This study examines patterns of gendered communication in spoken and written discourse within higher education and workplace settings, highlighting differences in lexical choices, politeness strategies, turn-taking, and discourse structuring. Using a qualitative approach, the research analyzes authentic interactional data to identify how male and female speakers navigate authority, collaboration, and relational goals. Findings reveal that gendered patterns are context-dependent, influenced by institutional norms, cultural expectations, and power dynamics, rather than fixed linguistic behavior. The study also shows that awareness of gendered language use has practical implications for professional communication, collaborative teamwork, and academic instruction. By linking sociolinguistic theory with applied research, the study contributes to understanding the intersection of language, gender, and social roles, offering insights for linguists, educators, and practitioners.